Obtenção das cerâmicas dielétricas BiTRWO6 (TR = Y, Gd ou Nd) por radiação de micro-ondas e sua aplicação em dispositivos eletrônicos - Rocha, Gilvan Nóbrega da (2012)
The mixture heat of the metal oxides may promote the formation of ceramic materials, depending on their dielectric properties and its crystalline structure may be used with electronic components for a variety of functions in electrical circuits. Heating method is directly related to the material properties. This work aims to use a commercial microwave oven modified to carry out reactions in the solid state, in order to promote the reaction between oxides of bismuth and tungsten with oxides of rare earths. The oxides of gadolinium, yttrium and neodymium were selected for the experiment, where the materials were BiGdWO6 dielectric ceramics, and BiYWO6 BiNdWO6. The proof of obtaining the phase ceramics and structural study of these were performed by means of X-ray diffraction (XRD) and infrared and Raman spectroscopy. It was also studied the electrical properties in order to evaluate the applicability of the material as electronic apparatus. Tests of materials for application as electronic components in the microwave region suggested, after the analysis of dielectric measurements, its use as microstrip and monopole antennas. The dielectric properties (permittivity and loss) of the samples proved to be attractive for capacitor applications and certainly for microelectronics devices, microwave (antenna for mobile phones, for example).